Antropocæn og automatiseringen af adfærd: En kritik af det liberale Danmarks teknologioptimisme - Andersen, Gregers (K&K - Kultur og Klasse, 2020)
This article critically describes the connection between digital and geophysical developments. In its first part it uses Felix Guattari’s notion of ‘planetary computerization’ to show how the global spreading of the personal computer should be understood as a deterritorialization of capitalist power, which accelerates global warming and the destruction of Earth’s ecosystems. In particular, it analytically unfolds how the global spreading of the personal computer advances an automatization of behavior, which leads to ‘auto-destructive’ consumerism. In the second and third part the article turns to Danish politics and the techno-optimism, which guided the two liberal governments, who ruled Denmark from June 2015 to June 2019. The article argues that these two governments embraced the prospect of accelerating automatization without taking into account how such an acceleration is highly likely to further increase the geophysical problems of the Anthropocene and produce increased inequality.